1984
DOI: 10.1111/j.1600-051x.1984.tb01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsurgical periodontal therapy

Abstract: Healing events following nonsurgical periodontal therapy in patients with periodontal pockets up to 12 mm deep were investigated. Incisors, cuspids and premolars in 16 patients were treated by plaque control and supra- and subgingival debridement using hand or ultrasonic instruments in a split mouth approach. The results were evaluated by recording of plaque scores, bleeding on probing, probing pocket depths and probing attachment levels. Minimal change in gingival conditions occurred during the initial 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
484
9
31

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 665 publications
(590 citation statements)
references
References 8 publications
66
484
9
31
Order By: Relevance
“…In patients with advanced periodontitis, this results in clinical reduction of pocket depths, gain of clinical attachment levels and reduc tion in bleeding scores in both moderate and deep pockets. 10,11 The principal aspect of the treatment is the removal of the com ponents of the subgingival plaque biofi lm, which have a major role in the initiation and progression of the disease. 12 Several studies have shown that the periodon topathogens can colonise other intraoral niches such as tongue dorsum, tonsils, saliva and other mucous membranes in addition to the periodontal pockets.…”
mentioning
confidence: 99%
“…In patients with advanced periodontitis, this results in clinical reduction of pocket depths, gain of clinical attachment levels and reduc tion in bleeding scores in both moderate and deep pockets. 10,11 The principal aspect of the treatment is the removal of the com ponents of the subgingival plaque biofi lm, which have a major role in the initiation and progression of the disease. 12 Several studies have shown that the periodon topathogens can colonise other intraoral niches such as tongue dorsum, tonsils, saliva and other mucous membranes in addition to the periodontal pockets.…”
mentioning
confidence: 99%
“…2 Numerous studies have reported significant improvements of clinical and microbial parameters following nonsurgical periodontal therapy. [3][4][5][6] Despite the fact that non-surgical periodontal treatment may result in significant clinical improvements in the great majority of cases, evidence indicates that none of the currently available instrumentation techniques are effective in completely eliminating subgingival bacterial biofilm. 7 These limitations may be attributed to several factors such as the complex anatomy of teeth (i.e.…”
Section: Biological Rationalementioning
confidence: 99%
“…Several reasons are proposed for this failure and they are 1) the amount of residual calculus being dependent on the size of the surface to be scaled; 2) with deeper pockets more irregularities are observed on the tooth surface; and 3) in deeper pockets the apical portion of the pocket is narrower making accessibility to the bottom of the pocket difficult with complete removal of calculus unlikely [29]. However, in an early paper, Badersten et al [30], NSPT showed some improvement in clinical attachment even in sites with probing pocket depth more than 7 mm. On the other hand, over the long-term there is a possibility of further attachment loss in the sites with deep residual probing depths particularly if combined with bleeding on probing [31].…”
Section: Non-surgical Periodontal Therapymentioning
confidence: 99%